Monopoly Capital: An Essay on the American Economic and Social Order - Johansen, Leif; Baran, Paul A.; Sweezy, Paul M. (Econometrica, 1969)
This landmark text by Paul Baran and Paul Sweezy is a classic of twentieth-century radical thought, a hugely influential book that continues to shape our understanding of modern capitalism.